Peran Mediasi Kepuasan Pelanggan Atas Pengaruh Relationship Marketing Dan Service Quality Terhadap Loyalitas Pelanggan - Novian avisena; Survival Survival; Adya Hermawati (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study aims to determine the mediating role of customer satisfaction on the influence of relationship marketing and service quality on customer loyalty (studies at the Grand Citihub Hotel @Kajoetangan, Malang City. The population in this study were all customers of the Grand Citihub Hotel @Kajoetangan Malang City who had used hotel services. The sampling technique used in this study is Nonprobability Sampling with a total of 100 respondents. And the data is processed through Smart Partial Least Square (PLS) software.The results of this study indicate that: (1) Relationship marketing is able to increase customer loyalty at Grand Citihub Hotel @Kajoetangan Malang City. (2) Service quality is able to increase customer loyalty of Grand Citihub Hotel @Kajoetangan Malang City. (3) Relationship marketing is not able to increase customer satisfaction at Grand Citihub Hotel @Kajoetangan, Malang City. (4) Service quality is able to increase customer satisfaction at Grand Citihub Hotel @Kajoetangan, Malang City. (5) Customer satisfaction is able to increase customer loyalty of Grand Citihub Hotel @Kajoetangan Malang City. (6) Customer satisfaction is unable to play a role in mediating the effect of relationship marketing on customer loyalty of Grand Citihub Hotel @Kajoetangan, Malang City. (7) Customer satisfaction is able to play a role in mediating partially (partial mediation) on the effect of service quality on customer loyalty Grand Citihub Hotel @Kajoetangan Malang City.